THE EFFECT OF INTERNAL AUDITORS AND INTERNAL CONTROL ON COMPANY PERFORMANCE (Case study in Sukoharjo Regency) - Murti, Bayu; Wijayanti, Anita; Masitoh, Endang (eBA Journal: Journal Economics, Bussines and Accounting, 2018)
The purpose of this study is (1) to determine the effect of internal auditors on Company Performance (2) to determine the effect of internal controls on company performance. This research was conducted in 4 manufacturing companies in Sukoharjo regency. The number of respondents in this study is 50 respondents from 50 questionnaires that have been distributed. Respondents in this study are internal auditor staff who work in a company. The method used is purposive sampling method. Data analysis method uses multiple linear regression analysis and the process of using SPSS 22. Determination of the coefficient of adjusted R Squared testing results of 0.37 indicates that 37% of the company's performance variables can be explained by internal auditor and internal control variables, while 63% is explained by factors other than research. From the tests that have been carried out f test and t-test, the research shows that (1) internal auditors affect the company's performance as evidenced by comparing the value of t count> t table at a significant 5% is 2,175> 2,0129 (2) internal control affects the company's performance with the proof proved by comparing the value of t count> t table at 5% significant is 4,751> 2,0129.